Respuesta del cultivo de la rosa (Rosa sp.), a la aplicación de Ca - Mg y B, mediante fertirrigación bajo condiciones de invernadero, en el cantón Cayambe, provincia de Pichincha - Zambrano Zambrano, Jorge Jacobo (2017)
VIII. SUMMARY In this research the answer cultivation rose (Rosa sp.), The application of Ca-Mg-B alone and combined by fertigation greenhouse conditions in the canton Cayambe, Pichincha province, was evaluated in order to evaluate the performance of growing rose against the different applications of these elements; identify which of these nutrients alone or combined presents the best performance in quality and economically analyze rosebush treatments. The Complete Random Design (DCA) was used with 7 treatments and three repetitions, giving a total of 21 experimental units. The total area of the experiment was 120,60 m2, the plot undergoes of 2,68 m2, 2,14 m2 useful area, the distance between roads and repeats 0,67 m. Atem length, stem diameter, length of flower bud vase life, stems export performance and domestic: the variables were evaluated. economic analysis was performed based on the performance of the number of stems export and national sale according to the value of the intended market, production costs of each treatment (fixed and variable) was made, then get the cost - benefit. Checking measures of treatments was performed using test Duncan Multiple Range 5% probability. The experimental results showed that: rosebush growing variety Angie, responded positively to the implementation of Ca, Mg and B elements; the combination of Ca + Mg + Mg + B and B, in fertigation, responded variables significantly in the long stem, stem diameter, button size, days and number of stems vase export; achieving significant results versus control and other treatments alone and in combination; fertigation treatments with Mg + B, Ca + Mg and Ca + Mg + B, the greatest economic return on the control (without application) was achieved.